"A Bureaucratic Trap:" Free, Prior and Informed Consent (FPIC) and Wind Energy Development in Juchitán, Mexico. Issue 4 (2nd October 2018) - Dunlap, Alexander
ABSTRACT: On November 2014, the first Free, Prior and Informed Consent (FPIC) consultation was called for the Eólica del Sur wind project in Juchitán de Zaragoza, Mexico. Lasting eight months, the consultation was responding not only to the UN International Labor Organization's (ILO) convention 169 that Mexico signed in 1990 but also to widespread uprisings against wind energy projects in the region. This article begins with an FPIC literature review, followed by sections examining the consultation in Juchitán, its spatial layout, the actors involved and its repressive atmosphere. The subsequent section analyzes the discursive techniques deployed by the FPIC technical committee (TC) which—despite unanswered questions and popular opposition to the wind energy project—granted project approval on 30 June 2015. The final section concludes that the FPIC consultation undermines Indigenous autonomy and serves as a counter-insurrectionary device, reinforcing a context of substantial political and economic asymmetry between state, corporate and elite interest and Indigenous fishermen and farmers. The FPIC consultation in Juchitán reinforced state power and simultaneously serves as a marketing platform for development projects, thereby creating an illusion of real dialogue, negotiation and, by extension, democratic decision making. Despite efforts to have the wind project approved, resistance groups' temporarily halted construction.